Genetic analysis and serum level of cartilage oligomeric matrix protein in patients with pseudoachondroplasia - Liu, Feng-xia; Li, Zhi-ling; Wei, Zhen-ji; Meng, Yan; Ren, Cui-ai; Zhang, Xu-de; Yu, Meng-xue; Huang, Shang-zhi (Chinese medical journal, 2010)
Background Pseudoachondroplasia （PSACH） is an autosomal-dominant osteochondrodysplasia due to mutations in the gene encoding cartilage oligomeric matrix protein （COMP）.Clinical diagnosis of PSACH is based primarily on family history, physical examination, and radiographic evaluation.There is evidence that decreased serum COMP concentration may serve as a diagnostic marker in PSACH.Here, we investigated the role of this gene and the serum COMP concentration in Chinese patients with PSACH.Methods A family with three patients and a sporadic case were recruited.Genomic and phenotypic data were recorded.The diagnosis of PSACH was made on the base of clinical evaluation.The genomic DNA was extracted from peripheral blood leukocytes.The 8-19 exons and flanking intron-exon boundary sequences of COMP were amplified by polymerase chain reaction （PCR） and screened for mutation by direct DNA sequencing.Serum COMP concentrations of 4 patients and age-compatible control group of 20 unrelated healthy subjects were analyzed on the basis of an ELISA Kit for human cartilage oligomeric matrix protein.Results A deletion （c.1447-1455del） was identified in exon 13 in the sporadic case.The mean serum COMP concentrations of four patients （3.12±2.28） were significantly lower than those of control group （10.86±2.21, P 〈0.05）.There was no overlap in the distribution of serum COMP concentration between PSACH patients and controls.Conclusions Mutations in COMP gene are responsible for the PSACH.Serum COMP concentration may be suggested as an additional diagnostic marker to aid clinical findings in suspected cases of PSACH.